QoS Forwarding on the Optical Internet Backbone Area Using R-IWDMTC Protocol - Addie Irawan, Hashim; R. Badlishah, Ahmad (2006)
This article describes the study of improving the proposed protocol called Receiverinitiated WDM Tree Construction (R-IWDMTC) protocol. The protocol has been introduced by Salvador et al. (Extended via Multi-protocol Label Switching (MPLS)) provides connection-oriented setup and multicast tree construction control for Optical Internet data forwarding in the network backbone area. The study has done several analysis and research to improve R-IWDMTC protocol to support quality and services (QoS) (differentiation and integration services). Several algorithms, schemes and techniques have been suggested in this study including several analyses. The study has focused on RTA link set-up and data forwarding. Discrete event simulator called OMNeT++ is used for modelling and analysis purposes and model of optical internet backbone area has been developed. The analysis were referred from the average access delay, percentage of loses, jitters and throughput of data (video, voice and text) that has been transferred between two end point via optical internet backbone area. The results were proved that the differentiation and integration technique could be applied in Optical Internet and gateway system by using R-IWDMTC protocol.